Pseudohypoaldosteronism Type 1 Newborn Patient with a Novel Mutation in SCNN1B - Seyhanli, Muhammed; Ilhan, Ozkan; Gumus, Evren; Bor, Meltem; Karaca, Meryem (Journal of Pediatric Intensive Care, 2020)
Pseudohypoaldosteronism is a rare disease characterized by resistance to aldosterone-targeted organs, hyponatremia, hyperkalemia, metabolic acidosis, and severe salt loss in hyperaldosteronism. Homozygous mutations in SCNN1A, SCNN1B, and SCNN1G genes were found to be responsible for the etiology. About 80 cases with molecular basis have been reported to date. In this case, a newborn patient admitted to our neonatal intensive care unit due to feeding problems was examined. The parents of the patient had a consanguineous marriage, and they had lost their three sons due to hyperkalemia. Since she had hyponatremia and hyperkalemia, congenital adrenal hyperplasia was primarily considered. Although the initial evaluation was made in this direction, the patient was diagnosed as pseudohypoaldosteronism type 1 with the findings obtained during the process such as dehydration, cortisol levels, adrenocorticotropic hormone levels, and negative CYP21A2 analysis result. This clinical diagnosis was confirmed by the novel homozygous frame-shift variant c.1245_1246insC (p.N416Qfs*35) in SCNN1B shown by gene analysis. In this report, we seek to emphasize that aldosterone deficiency should be one of the first diagnoses to be considered in neonatal patients with hyponatremia, hyperkalemia, metabolic acidosis, and dehydration.
Keywords: pseudohypoaldosteronism; hyperkalemia; SCNN1B